(untitled) (Baghdad Science Journal, 2019)
The most popular medium that being used by people on the internet nowadays is video streaming. Nevertheless, streaming a video consumes much of the internet traffics. The massive quantity of internet usage goes for video streaming that disburses nearly 70% of the internet. Some constraints of interactive media might be detached; such as augmented bandwidth usage and lateness. The need for real-time transmission of video streaming while live leads to employing of Fog computing technologies which is an intermediary layer between the cloud and end user. The latter technology has been introduced to alleviate those problems by providing high real-time response and computational resources near to the client at the network boundary. The present research paper proposes priority weighted round robin (PWRR) algorithm for streaming operations scheduling in the fog architecture. This will give preemptive for streaming live video request to be delivered in a very short response time and real-time communication. The results of experimenting the PWRR in the proposed architecture display a minimize latency and good quality of live video requests which has been achieved with bandwidth changes as well as meeting all other clients requests at the same time